Ação rescisória por violação da norma jurídica - Cramer, Ronaldo (2010)
This work aims to study the main controversial aspects of rescission action on the basis of item V of art. 485 of the Civil Procedure Code or simply rescission action for violation of rule of law. To reach the central theme, I choose to analyze the assumptions of no place of rescission action: sentence and res judicata. Also examine, in general, the rescission action and all its assumptions relevant. Begin the work studying the sentence, their effects and their classification. Dedicate special attention to the new concept of the sentence and the thesis of sentence partial. Then, I analyze all the contours of res judicata, highlighting its constitutional protection and the controversy over what they espouse its relativity. After res judicata, study the rescission action, your chances of your required and procedure established by law. Examined the rescission action, I discuss the focus of this study: the rescission action for violation of the rule of law. In this part of the work, I exam the interpretation of the rule of section V and the most controversial features of this action. Finally, summarize the key ideas of this study